2014
DOI: 10.3389/fped.2014.00106
|View full text |Cite
|
Sign up to set email alerts
|

Early Visual Attention in Preterm and Fullterm Infants in Relation to Cognitive and Motor Outcomes at School Age: An Exploratory Study

Abstract: Objective: Preterm infants are exposed to the visual environment earlier than fullterm infants, but whether early exposure affects later development is unclear. Our aim was to investigate whether the development of visual disengagement capacity during the first 6 months postterm was associated with cognitive and motor outcomes at school age, and whether associations differed between fullterms and low-risk preterms.Method: Seventeen fullterms and ten low-risk preterms were tested in a gaze shifting task every 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 68 publications
1
8
0
Order By: Relevance
“…In 80 low-risk late PT with a GA between 34.0 and 36.9 weeks assessed at birth and at term equivalent age, some aspects of visual abilities at term equivalent age such as attention at distance and ability to discriminate black/white stripes showed more mature findings in late PT infants than FT infants. This interesting point of view was reported by several authors that emphasized how the effects of the early visual "hyperstimulation" were a driving force to promote visual development (Sansavini, Guarini, & Caselli, 2011;Hitzert, van Braeckel, Bos, & Hunnius, 2014). Our findings might suggest an influence on visual and visuomotor skills achievement played by gender rather than prematurity, being these skills poorer not only in male infants born with moderate prematurity but also in FT ones.…”
Section: Discussionsupporting
confidence: 77%
“…In 80 low-risk late PT with a GA between 34.0 and 36.9 weeks assessed at birth and at term equivalent age, some aspects of visual abilities at term equivalent age such as attention at distance and ability to discriminate black/white stripes showed more mature findings in late PT infants than FT infants. This interesting point of view was reported by several authors that emphasized how the effects of the early visual "hyperstimulation" were a driving force to promote visual development (Sansavini, Guarini, & Caselli, 2011;Hitzert, van Braeckel, Bos, & Hunnius, 2014). Our findings might suggest an influence on visual and visuomotor skills achievement played by gender rather than prematurity, being these skills poorer not only in male infants born with moderate prematurity but also in FT ones.…”
Section: Discussionsupporting
confidence: 77%
“…A total of 45 studies met all the inclusion criteria. Executive function data were provided by 35 of these studies (3360 children born preterm/low birthweight and 2812 term‐born controls) either in the study paper or after a request for additional data sent to the authors . The characteristics and main study results are given in (Tables SI, SII, and SIII, online supporting information; working memory, inhibition, and cognitive flexibility respectively).…”
Section: Resultsmentioning
confidence: 99%
“…Longitudinal studies have also convincingly demonstrated that infant measures of complex attention, memory, and inhibition skills are predictive of EF measures in later childhood. For example, individual differences in infant measures reflecting the ability to both sustain and flexibly shift attention are predictive of EF during childhood and adolescence (Cuevas & Bell, 2014; Johansson, Marciszko, Gredebäck, Nyström, & Bohlin, 2015; Papageorgiou et al, 2014; Sigman, Cohen, & Beckwith, 1997; Sigman, Cohen, Beckwith, Asarnow, & Parmelee, 1991), both in typically developing infants and in at-risk populations (Hitzert, Van Braeckel, Bos, Hunnius, & Geuze, 2014; Rose, Feldman, Jankowski, & Van Rossem, 2012). These predictive relationships typically remain even after controlling for general intellectual ability (e.g.…”
Section: Frontal Lobe Contributions To Infant Cognitionmentioning
confidence: 99%
“…In a series of elegant, longitudinal studies beginning in infancy, Rose, Feldman, and Jankowski demonstrated that higher-level attentional processes are altered across the first years of life in higher-risk PT infants, contributing to later differences in adolescent EF skills (see Rose, Feldman, & Jankowski, 2016 for summary). Interestingly, lower-risk PT infants may show a slight “benefit” in attentional processing earlier in development; lower-risk PT infants are faster at disengaging and shifting attention than their full-term peers, although this “benefit” in attention typically disappears by 4–6 months of age (Hitzert et al, 2015, 2014; Hunnius, Geuze, Zweens, & Bos, 2008). Other studies have also found that lower-risk PT infants perform better on early attention measures than their higher-risk PT peers (Landry & Chapieski, 1988; Reuner, Weinschenk, Pauen, & Pietz, 2015).…”
Section: Early Adverse Experiences and Pfc Developmentmentioning
confidence: 99%